Universal Design In Inclusive Education: Opportunities, Approaches, And Methodological Foundations - Nazarova Dildora Asatovna (Genius Journals, 2025)
A contemporary education system must be structured to accommodate each student’s unique needs, individual developmental level, and social context. The concept of inclusive education focuses on ensuring that students with disabilities, as well as those facing psychological or social challenges, can fully participate in a mainstream education environment. This goal requires not only infrastructural adaptations but also a rethinking of teaching methods, assessment systems, educational resources, and pedagogical approaches. In this context, the Universal Design approach holds particular significance. The Universal Design for Learning (UDL) model aims to create an educational setting that meets the diverse needs of all learners. This paper analyzes the theoretical and methodological underpinnings, advantages, and practical applications of universal design in the process of inclusive education.
Keywords: UDL model; methods; approach